Penerapan Sistem Informasi Akuntansi Siklus Penjualan PT Asaindo Jaya Persada Perumahan Star Land Regency - Aisyah Brillianta; Achmad Wicaksono (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This study aims to analyze the implementation of Accounting Information Systems (AIS) in the sales cycle at PT Asaindo Jaya Persada, a real estate company located in Sidoarjo. With the rapid development of information technology, AIS has become an essential element in assisting companies in recording, processing, and presenting financial information efficiently. This research identifies the challenges faced by the company in managing the sales cycle, which includes various stages from promotion to the handover of housing units. The research employs a qualitative method, with data collection through semi-structured interviews and analysis of documents related to the sales cycle. The findings indicate that although the sales cycle at PT Asaindo Jaya Persada operates systematically, there are obstacles such as delays in the collection and processing of mortgage documents and a lack of coordination among the marketing team, financial staff, and banks. To address these challenges, the study recommends digitalization of processes and consumer education as solutions to enhance efficiency and customer satisfaction. Additionally, suggestions for future research include conducting quantitative studies to evaluate the efficiency of AIS in the sales cycle and integrating more advanced digital technologies to improve transparency and accountability. With these measures, it is hoped that PT Asaindo Jaya Persada can enhance its sales cycle performance and achieve better business objectives.